Transmitter diversity for OFDM systems and its impact on high-rate data wireless networks. - Ye Li
Transmitter diversity and down-link beamforming can be used in high-rate data wireless networks with orthogonal frequency division multiplexing (OFDM) for capacity improvement. We compare the performance of delay, permutation and space-time coding transmitter diversity for high-rate packet data wireless networks using OFDM modulation. For these systems, relatively high block error rates, such as 10%, are acceptable assuming the use of effective automatic retransmission request (ARQ). As an alternative, we also consider using the same number of transmitter antennas for down-link beamforming as we consider for transmitter diversity. The investigation indicates that delay transmitter diversity with quaternary phase-shift keying (QPSK) modulation and adaptive antenna arrays provides a good quality of service (QoS) with low retransmission probability, while space-time coding transmitter diversity provides high peak data rates. Down-link beamforming together with adaptive antenna arrays, however, provides a higher capacity than transmitter diversity for typical mobile environments
Keywords: ARQ; OFDM modulation; OFDM systems; QPSK; QoS; Adaptive antenna arrays; Automatic retransmission request; Capacity; Cellular radio; Delay; Down-link beamforming; High block error rates; High peak data rates; High-rate data wireless networks; High-rate packet data wireless networks; Low retransmission probability; Mobile environments; Orthogonal frequency division multiplexing; Performance; Permutation; Quality of service; Quaternary phase-shift keying; Space-time coding transmitter diversity; Transmitter antennas